2021
DOI: 10.17159/2413-3221/2021/v49n2a11213
|View full text |Cite
|
Sign up to set email alerts
|

Recognising indigenous vegetables as potential contributors to livelihoods development: a case of two district municipalities in northern KwaZulu-Natal

Abstract: South Africa is a food sufficient country. Native South Africans, however, continue to suffer from food insecurity at a household level, even under contemporary democratic leadership. Influenced by the COVID-19 pandemic, the study was conducted to determine the role of indigenous vegetables in rural livelihoods in the two selected district municipalities of northern KwaZulu-Natal, namely iLembe District Municipality (IDM) and the King Cetshwayo District Municipality (KCDM). A purposive sample which consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, most of the IVs (Table 1) have higher values of protein, fibre, carbohydrate, calcium, potassium, magnesium and β-carotene which are Table 2 Summary of respondent's perceived benefit of IVs Perceived benefits key sources of most of the perceived benefits. Similar benefits were highlighted by respondents for IVs elsewhere [46,75]. IVs may potentially improve overall wellbeing in marginal sectors of the community and nutrition in communities with lower income levels [76].…”
Section: Perceived Benefits Of Ivsmentioning
confidence: 78%
“…For example, most of the IVs (Table 1) have higher values of protein, fibre, carbohydrate, calcium, potassium, magnesium and β-carotene which are Table 2 Summary of respondent's perceived benefit of IVs Perceived benefits key sources of most of the perceived benefits. Similar benefits were highlighted by respondents for IVs elsewhere [46,75]. IVs may potentially improve overall wellbeing in marginal sectors of the community and nutrition in communities with lower income levels [76].…”
Section: Perceived Benefits Of Ivsmentioning
confidence: 78%
“…When asked how farming impacts their livelihoods, the following responses were recorded from some of the farmers: The extracts above indicate the important role of agriculture in rural communities. The sociodemographic status of these communities indicated that most farmers have not received formal education and were unemployed (Qwabe, Zwane, and Swanepoel, 2021). Based on this finding, the assertions made by farmers prove true that due to their socio-economic conditions it would be difficult to navigate through life as pension money alone cannot guarantee a sustainable livelihood.…”
Section: Impact Of Agriculture On Rural Livelihoodsmentioning
confidence: 93%
“…In total, thirty rural farmers took part in the study. With specific reference to IDM and KCDM, previous research shows that most people are unemployed and depend on government grants (Qwabe, Zwane & Swanepoel, 2021). Therefore, the researchers attempted to find the nexus between extension services and livelihood development.…”
Section: Study Sites and Samplingmentioning
confidence: 99%
“…In this particular study, thematic synthesis (Thomas & Harden, 2008) will be used to generate themes that are aligned to the research objectives of this inquiry. The COSTAQDA, a cloud-based qualitative data analysis software that is suitable for literature-based inquiry will be used Qwabe, 2021).…”
Section: Extracting and Synthesizing Datamentioning
confidence: 99%